La orientación vocacional en los estudiantes de la unidad educativa “Salcedo” a través de la educomunicación - Chasig Quisaguano, Edgar Damian (2017)
The present research was carried out in Salcedo Elementary School, during the academic period September 2016 – July 2017, in which the educative community performed, specifically the third years of bachillerato, taking into account that educomunicacion has been into a paradigm into topics of making decisions of academia and a prior point in the vocational orientation being the direct beneficiaries as students as teachers. From the tics development, the information access worldwide has been easy by which the social media has reached a communication system which allows satisfying the students’ expectatives through the informative, educative and cultural contents. In the present research was necessary to make new pedagogical methodological techniques which allow to educomunicacion introduce as learning and process tool. the techniques used were survey and observation….